Ion pairing in ionic liquids controls the Corannulene reduction mechanism - Tanner, E; Compton, R; Batchelor-McAuley, C; Foong, K; Hossain, M; Aldous, L (American Chemical Society, 2016)
The electroreduction of corannulene (C20H10) has been investigated in a Room Temperature Ionic Liquid (RTIL) for the first time. In the RTIL 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide ([Bmpyrr][NTf2]) the resultant voltammetry shows a peak-to-peak separation of 100 mV, and this separation does not vary with scan rate (as predicted by a simple E mechanism). We propose a square scheme that is capable of accurately describing this behaviour. Specifically, the use of a square scheme takes into account the affect of ion pairing between the ionic liquid cation and the corannulene anion on the overall reaction mechanism. Importantly, investigation in acetonitrile with a range of conventional electrolytes does not display the trends observed in the RTIL. This result likely provides a general insight into all RTILs as a class of electrolyte, because of the high concentration of ions and the proclivity of RTILs to ion-pair.